227k views
0 votes
Please answer asap!

the recursive rule for a geometric sequence is given. a1=2 an=1/3an−1 enter the explicit rule for this sequence.

1 Answer

4 votes

ANSWER

The explicit rule is:


a_n=2{( (1)/(3) )}^(n - 1)

Step-by-step explanation

The recursive rule is


a_1=2

and


a_n= (1)/(3) a_ {n - 1}

We can rewrite to get,


\frac{a_n}{a_ {n - 1}} = (1)/(3)

This implies that, the constant ratio is:


r = (1)/(3)

The explicit rule is given by:


a_n=a_1 {r}^(n - 1)

We substitute the values to obtain, the explicit rule as:


a_n=2{( (1)/(3) )}^(n - 1)

User Willona
by
4.9k points